2019
DOI: 10.3892/ijo.2019.4861
|View full text |Cite
|
Sign up to set email alerts
|

Expression profile‑driven discovery of AURKA as a treatment target for liposarcoma

Abstract: Liposarcoma (LPS) is one of the most frequently reported type of soft-tissue sarcoma (STS). Well-differentiated (WD) LPS and dedifferentiated (DD) LPS are the two most common subtypes. Chemotherapy has been considered to be ineffective in LPS, and novel treatment agents are thus necessary. In this study, we reanalyzed two published microarray data sets of LPS. By comparing the top 50 upregulated genes in DD LPS in both sets of data, we identified 12 overlapping genes. Of note, the top five gene sets enriched i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Aurora A and B kinases inhibition by RNAi and pharmacological treatment with a pan Aurora kinase inhibitor AMG 900 reduced tumor proliferation and cell survival in liposarcoma cell lines [96]. MLN8237, an Aurora A kinase inhibitor, showed G2/M phase cell cycle arrest and a cytotoxic effect leading to apoptosis of tumor cells with a significant synergistic effect with chemotherapy agents against LPS, except for cisplatin [97].…”
Section: Aurora Kinases Inhibitormentioning
confidence: 99%
“…Aurora A and B kinases inhibition by RNAi and pharmacological treatment with a pan Aurora kinase inhibitor AMG 900 reduced tumor proliferation and cell survival in liposarcoma cell lines [96]. MLN8237, an Aurora A kinase inhibitor, showed G2/M phase cell cycle arrest and a cytotoxic effect leading to apoptosis of tumor cells with a significant synergistic effect with chemotherapy agents against LPS, except for cisplatin [97].…”
Section: Aurora Kinases Inhibitormentioning
confidence: 99%
“…Besides, Liu et al pointed that PABPC4 likely played a role in the pathogenesis of colorectal cancer [57]. In various types of cancers, numerous studies have now documented a link between EIF4A3, SMC3, ESPL1, CDC25B, CCNA2, or AURKA and their response to therapy [58][59][60][61][62][63]. For the downregulation core gene THBS3, conversely, it was expressed at significantly 9 Disease Markers high levels in osteosarcoma, which was a predictor of worse OS at diagnosis [64].…”
Section: Disease Markersmentioning
confidence: 99%
“…tumors regulates treatment resistance not only via tumor polyploidization, but also via expansion of impaired TAMs through GDF15 production. Some studies have also shown regulation of production of cytokines and chemokines by AURKA [ 25 , 26 ], although AURKA is a protein kinase mainly regulating cell cycle. However, locking AURKA with MLN8237 or siRNAs abrogates these adverse events, and successfully elicits anti-tumor immunity in the ascites models.…”
Section: Discussionmentioning
confidence: 99%